Integration of heterogeneous databases for medical experts - Azmi Murad, Masrah Azrifah; A. Jabar, Marzanah; Sidi, Fatimah; Kadiman, Suhaini; O. K. Rahmat, Rahmita Wirza (IEEE, 2012)
This paper presents an initial work on the conceptual architecture of medical databases integration. The problem with current medical institutions are that most of them have variety of systems across various departments where most of the systems have existing and incompatible database management system that are tied together in a network. All these systems stored patients' information in an isolated and stand-alone environment and as such, a user who wish to use the system would have to log-in and log-out from one system to another in order to monitor or trace a patient's medical record. To overcome the problem above, we proposed an integration of heterogeneous medical databases that can eliminate data duplication and save cost, and at the same time can assist medical experts either before or after a surgery.